A Socio-Ecological Approach to Addressing Digital Redlining in the United States: A Call to Action for Health Equity - McCall, Terika; Asuzu, Kammarauche; Oladele, Carol R.; Leung, Tiffany I.; Wang, Karen H. (Frontiers in Digital Health, 2022)
Physical distancing requirements due to the coronavirus (COVID-19) pandemic has increased the need for broadband internet access. The World Health Organization defines social determinants of health as non-medical factors that impact health outcomes by affecting the conditions in which people are born, grow, work, live, and age. By this definition broadband internet access is a social determinant of health. Digital redlining – the systematic process by which specific groups are deprived of equal access to digital tools such as the internet – creates inequities in access to educational and employment opportunities, as well as healthcare and health information. Although it is known that internet service providers systematically exclude low-income communities from broadband service, little has been done to stop this discriminatory practice. In this paper, we seek to amplify the call to action against the practice of digital redlining in the United States, describe how it contributes to health disparities broadly and within the context of the COVID-19 pandemic, and use a socio-ecological framework to propose short- and long-term actions to address this inequity.